A novel low-temperature absorption–compression cascade refrigeration system. (22nd January 2015) - Xu, Yingjie; Chen, FuSheng; Wang, Qin; Han, Xiaohong; Li, Dahong; Chen, Guangming
Abstract: This paper presents a novel absorption–compression cascade refrigeration system, which can reach an evaporating temperature of −170 °C. In the cascade system, the refrigerant of compression subsystem (CS) is subcooled by the refrigerant of low-grade heat driven absorption subsystem (AS) to reduce the electric power consumption. Theoretical and experimental investigations were carried out over the CS evaporating temperature ranging from −100 to −170 °C and operating parameters were given. At the CS evaporating temperature of −170 °C, when AS provided a low-grade cooling capacity of 164.8 W to CS, a decrease of 2.5 °C in CS evaporating temperature or an increase of 32.3 W in high-grade cooling capacity of CS were observed. Meanwhile, in CS, the discharge temperature and pressure decreased, while the suction pressure increased. These beneficial results not only verified the feasibility of the system, but also revealed the application potential of the system in the future. Highlights: A low-temperature absorption–compression cascade refrigeration system is presented. Thermodynamic calculations are conducted to analyze the system performance. An experimental rig is developed and experimental investigations are carried out. Dynamic and steady-state parametric studies are conducted for this system.